Study on incidences, risk factors and bacterial populations involved in subclinical mastitis cases in the conventional vis-à-visorganic dairy farming under small holder system in Indian Sundarban region - Halder, Rinika; Bandyopadhyay, Samiran; GHOSH, SARBASWARUP (Indian Journal of Dairy Science, 2024)
Organic dairy farming is being promoted in Indian Sundarban region through the ‘Women Milk Producers’ Cooperative Society’ under the aegis of Sundarban Milk Union of West Bengal. The present study was undertaken to investigate the prevalence of sub clinical mastitis (SCM) in dairy herds maintained by small holders in two production system (organic vis-à-visconventional). Total numbers of 34 dairy farmers were selected for the study. Out of the 34 numbers of farmers, 50% farmers (n =17) had adopted organic milk production practices and the remaining (n = 17) farmers used to practice conventional dairy farming. Callifornia Mastitis Test (CMT) kit was used to evaluate incidences of SCM. A semi-structured questionnaire was used for analysis of associated management risk factors for SCM.Positive milk samples from organic growers were subjected to microbial analysis and antibiogram. Data was analyzed for descriptive statistics by SPSS program v. 20.0. Results revealed that the incidences of SCM is not significantly (p<0.05) different in organic (35.3%) and conventional (29.4%) dairy production system, indicating chronic and long standing infection in udders. Besides, no significant (p<0.05) difference between the two production system was observed in management risk factors associated with SCM. It was found that Staphylococcus aureus is the causative organism responsible for SCM under organic dairy production system in the study area. It can be concluded that to reduce high rate of SCM in the region, regular monitoring of udder health with holistic approach is necessary.